2017
DOI: 10.1111/zsc.12272
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics and evolutionary history of catenotaeniid cestodes (Cyclophyllidea)

Abstract: Phylogenetic relationships, evolutionary history and systematics of tapeworms of the family Catenotaeniidae were studied using nucleotide sequences of the partial 28S nuclear rDNA (ca. 1,500 bp) and mitochondrial 12S–16S DNA (ca. 820 bp) genes. The tapeworm material consists of 29 species, including type species of the genera Catenotaenia Janicki, 1904, Catenotaenioides Haukisalmi, Hardman and Henttonen, 2010, Pseudocatenotaenia Tenora, Mas‐Coma, Murai and Feliu, 1980, Skrjabinotaenia Akhumyan, 1946, Meggittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In this study, depending on observing the morphological characteristics, it has been reported two of unidentified species of cestodes from small intestine of house mice in Kalar district/ Iraq with the overall prevalence rate of 12.82 (15 out of 117). These species were potentially linked to the family Cataenotaenidae Spasskii, 1950 (Haukisalmi et al 2018;Owen 1976). It is a family of cyclophyllidean cestodes, which involves 37 species belonging to seven genera and they are parasites of rodent (host specific) and were not found to infect humans, reviewed in Haukisalmi et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, depending on observing the morphological characteristics, it has been reported two of unidentified species of cestodes from small intestine of house mice in Kalar district/ Iraq with the overall prevalence rate of 12.82 (15 out of 117). These species were potentially linked to the family Cataenotaenidae Spasskii, 1950 (Haukisalmi et al 2018;Owen 1976). It is a family of cyclophyllidean cestodes, which involves 37 species belonging to seven genera and they are parasites of rodent (host specific) and were not found to infect humans, reviewed in Haukisalmi et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…These species were potentially linked to the family Cataenotaenidae Spasskii, 1950 (Haukisalmi et al 2018;Owen 1976). It is a family of cyclophyllidean cestodes, which involves 37 species belonging to seven genera and they are parasites of rodent (host specific) and were not found to infect humans, reviewed in Haukisalmi et al (2018). Significant differences were observed in female than in male (P= 0.045), could be related to suppressed immune response of female during pregnancy (Engels et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations